2014
DOI: 10.3109/17549507.2014.941934
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pre-school children’s pretend play and subsequent development of semantic organization and narrative re-telling skills

Abstract: The study provides evidence that the quality of pretend play in 4-5 year olds is important for semantic organization and narrative re-telling abilities in the school-aged child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…Indeed, the important factor related to a child's ability to bring more non-literal, fantasy elements into play and to display more interactions with others during play has been reported to be the child's level of verbal ability. 39,40 In addition, our findings highlight that the CARS score should be used as intended, that is, to measure the severity of ASD symptoms and not functional impairment. Our study underlines the importance of the inclusion of not only severity of autism behaviors but also verbal comprehension when targeting interventions in children with ASD.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, the important factor related to a child's ability to bring more non-literal, fantasy elements into play and to display more interactions with others during play has been reported to be the child's level of verbal ability. 39,40 In addition, our findings highlight that the CARS score should be used as intended, that is, to measure the severity of ASD symptoms and not functional impairment. Our study underlines the importance of the inclusion of not only severity of autism behaviors but also verbal comprehension when targeting interventions in children with ASD.…”
Section: Discussionmentioning
confidence: 84%
“…For example, specific skills in pretense may have influenced the amount of negotiation and enactment observed. Future studies should investigate how children's individual performance in pretending, for example, using an index of the quality of play such as the CHIPPA (Stagnitti & Lewis, ), is associated with children's pretend play in peer interactions. Children's levels of emotional development, for example, individual differences in emotion understanding or expression, may also have individual or dyadic influences on pretend play behaviors (e.g., amity, Dunn & Hughes, ); however, these were not considered in the present study.…”
Section: Limitationsmentioning
confidence: 99%
“…Karniol () has argued that pretense is essentially both a social and linguistic phenomenon, relying on referential intersubjectivity and pragmatic inferencing regarding the “truth value” of utterances involving pretense. Considering peer social pretense, in particular the “negotiation” and “enactment” behaviors discussed above, require children to use linguistic competence to understand, direct, and act upon their peers’ implicit or explicit mental states (Trawick‐Smith, ), a handful of studies have looked at links between pretend play and the higher level aspects of linguistic development that such interactions require as pretend play increases in complexity, with a focus, in particular, on narrative abilities (e.g., Dunn & Cutting, ; Stagnitti & Lewis, ). In the current study, we built on existing research by considering both sentence‐level receptive and expressive language ability.…”
Section: Introductionmentioning
confidence: 99%
“…It takes 30 minutes for children aged four to seven and 18 minutes for 3‐year‐olds (Stagnitti, 2007, 2019). Relations to other variables have confirmed that ChIPPA results relate a child's social competence (Uren & Stagnitti, 2009), language and narrative (Stagnitti & Lewis, 2015), and theory of mind (Lin et al, 2017).…”
Section: Methodsmentioning
confidence: 83%